2021
DOI: 10.3389/fimmu.2021.718005
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Macrophage Crosstalk Initiates Sterile Inflammation in Embryonic Skin

Abstract: Macrophages are highly responsive to the environmental cues and are the primary responders to tissue stress and damage. While much is known about the role of macrophages during inflammatory disease progression; the initial series of events that set up the inflammation remains less understood. In this study, we use next generation sequencing (NGS) of embryonic skin macrophages and the niche cells - skin epithelia and stroma in the epidermis specific knockout of integrin beta 1 (Itgβ1) model to uncover specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…As reported previously, loss of integrin beta1 (itgβ1) from the epidermal compartment in mouse embryonic skin (cKO), leads to an augmentation of an inflammatory response characterized by increased macrophage cell infiltration and pro-remodeling fate acquisition (Kurbet et al, 2016 ; Bhattacharjee et al, 2021 ). However, the key metabolic pathways augmented by the epidermal compartment upon loss of itgβ1 remains to be uncovered.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…As reported previously, loss of integrin beta1 (itgβ1) from the epidermal compartment in mouse embryonic skin (cKO), leads to an augmentation of an inflammatory response characterized by increased macrophage cell infiltration and pro-remodeling fate acquisition (Kurbet et al, 2016 ; Bhattacharjee et al, 2021 ). However, the key metabolic pathways augmented by the epidermal compartment upon loss of itgβ1 remains to be uncovered.…”
Section: Resultsmentioning
confidence: 75%
“…We and others have shown that macrophages, an innate immune cell types, are the earliest responders to inflammatory cues in tissues (Kurbet et al, 2016 ; Bhattacharjee et al, 2021 ; Delavary et al, 2011 ). These macrophages exacerbate inflammation by acquiring an M2-like fate that cause exacerbated degradation the extra-cellular matrix by increased MMP synthesis.…”
Section: Introductionmentioning
confidence: 96%
“…Stem Cells International Additionally, since it is not just about the individual cell behavior and cell crosstalk and interaction are involved, an in vivo study would expand our horizon for an integrative understanding of view of the bone repair and regeneration process. Recently, environmental cells, such as immune cells, endothelial cells, and pericytes, have been recognized to cooperate with tissue cells to facilitate tissue repair [63][64][65][66].…”
Section: Effects Of Physical Exercise On Bone Repairmentioning
confidence: 99%
“…We previously reported that under sterile inflammatory conditions, the skin resident macrophages acquire an enhanced proremodeling fate that leads to degradation of the extracellular matrix (3). This alternative fate acquisition by the macrophages leads to progression of the diseased condition through exacerbated ECM disruption (4). Interestingly, metabolic remodeling has been shown to complement fate decision in immune cells (5,6).…”
Section: Main Textmentioning
confidence: 99%
“…As reported previously, loss of integrin beta1 (itg1) from the epidermal compartment in mouse embryonic skin, leads to augmentation of an inflammatory response characterized by increased macrophage cell infiltration and pro-remodeling fate acquisition (3,4). To gain insights into the metabolic states of macrophages and its niche cells, we used a previously generated NGS data from the epidermis, macrophages and fibroblasts of WT and itg1cKO embryonic skin and identified differentially expressed metabolic pathways in cKO epidermis (4).…”
Section: Main Textmentioning
confidence: 99%